Desarrollo, políticas, instituciones y poder - Pacheco Romero, Luis Santiago (2015)
Discussion on development goes on for decades in the international academic circles. There’s no agreement not even in how it should be defined. As regards how to move forward in the path of development, focus is centered in public policies. Analysts, however, are more concerned about the management of policies. This diminishes thinking on policies themselves, on their foundations. In that area, social sciences turn out to perform their task. Out of their research findings, theoretical approaches are derived, which may be divergent among themselves. From a general point of view, the particular approach which turns out to be applied depends on the character of the institutions prevalent in the particular society. Institutions may be either conservative or transforming. To have one or the other character depends on the political elite orientation. This takes us to the dilemma science or power. Power will disentangle itself from science if a conservative elite succeeds in attaining a dominant position. Political change will take place when there is an external context prone to change and when a domestic elite favourable to change with a sustainable proposal in mind is made up.